Danish Arctic Expeditions, 1605 to 1620, Volume 2, The Expedition of Captain Jens Munk to Hudson’s Bay in Search of a North-West Passage in 1619–20 In Two Books - Gosch, Christian Carl August 1832-1913 (Cambridge University Press, 1897)
The publications of the Hakluyt Society (founded in 1846) made available edited (and sometimes translated) early accounts of exploration. The first series, which ran from 1847 to 1899, consists of 100 books containing published or previously unpublished works by authors from Christopher Columbus to Sir Francis Drake, and covering voyages to the New World, to China and Japan, to Russia and to Africa and India. This 1897 volume contains the first English translation of Jens Munk's Navigatio Septentrionalis, his account of the Danish expedition of 1619–1620 in search of a North-West Passage to Asia. They reached Hudson's Bay and explored it, producing the first map to show the whole area. However, they were poorly prepared for the conditions there, and almost all the crew died from cold, hunger or disease. They returned to Denmark the following year, and although another expedition was planned, it did not take place
Title from publisher's bibliographic system (viewed on 15 Dec 2015)